CO(2) electrochemical catalytic reduction with a highly active cobalt phthalocyanine - Wang, Min (Nat Commun, 2019)
Molecular catalysts that combine high product selectivity and high current density for CO(2) electrochemical reduction to CO or other chemical feedstocks are urgently needed. While earth-abundant metal-based molecular electrocatalysts with high selectivity for CO(2) to CO conversion are known, they are characterized by current densities that are significantly lower than those obtained with solid-state metal materials. Here, we report that a cobalt phthalocyanine bearing a trimethyl ammonium group appended to the phthalocyanine macrocycle is capable of reducing CO(2) to CO in water with high activity over a broad pH range from 4 to 14. In a flow cell configuration operating in basic conditions, CO production occurs with excellent selectivity (ca. 95%), and good stability with a maximum partial current density of 165 mA cm(−2) (at −0.92 V vs. RHE), matching the most active noble metal-based nanocatalysts. These results represent state-of-the-art performance for electrolytic carbon dioxide reduction by a molecular catalyst.